Calculation of the Reliability of Helical Gear in Wind Turbine Gearbox Under Fatigue Pitting - Lin Feng; Wang Wei; Li Jianmin; Fang Zhigang; Dou Yiyi; Zeng Hanya; Yin Jie (Jixie chuandong)
The third stage helical gear of wind turbine gearbox is high-speed heavy-duty gear and it has high maintenance cost and high requirement for reliability. The fatigue pitting is one of the most common failures,which will make the reliability decline. The finite element model of helical gear with pitting corrosion is established. The stress spectrum is calculated and the reliability of helical gears with different pitting diameters and numbers are obtained under the effect of the wind field measured torque spectrum. The results show that the reliability of gear declines with the increase of pitting diameter,with the increasing number of pitting corrosion,the reliability is remarkably declining.